Pak2 Regulation of Nrf2 Serves as a Novel Signaling Nexus Linking ER Stress Response and Oxidative Stress in the Heart - Binder, Pablo; Nguyen, Binh; Collins, Lucy; Zi, Min; Liu, Wei; Christou, Foteini; Luo, Xiaojing; Hille, Susanne S.; Frey, Norbert; Cartwright, Elizabeth J.; Chernoff, Jonathan; Müller, Oliver J.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Endoplasmic Reticulum (ER) stress and oxidative stress have been highly implicated in the pathogenesis of cardiac hypertrophy and heart failure (HF). However, the mechanisms involved in the interplay between these processes in the heart are not fully understood. The present study sought to determine a causative link between Pak2-dependent UPR activation and oxidative stress via Nrf2 regulation under pathological ER stress. We report that sustained ER stress and Pak2 deletion in cardiomyocytes enhance Nrf2 expression. Conversely, AAV9 mediated Pak2 delivery in the heart leads to a significant decrease in Nrf2 levels. Pak2 overexpression enhances the XBP1-Hrd1 UPR axis and ameliorates tunicamycin induced cardiac apoptosis and dysfunction in mice. We found that Pak2 deletion and altered proteostasis render Nrf2 detrimental by switching from its antioxidant role to renin-angiotensin aldosterone system (RAAS) gene regulator. Mechanistically, Pak2 mediated Hrd1 expression targets Nrf2 for ubiquitination and degradation thus preventing its aberrant activation. Moreover, we find a significant increase in Nrf2 with a decrease in Pak2 in human myocardium of dilated heart disease. Using human-induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs), we find that Pak2 is able to ameliorate Nrf2 induced RAAS activation under ER stress. These findings demonstrate that Pak2 is a novel Nrf2 regulator in the stressed heart. Activation of XBP1-Hrd1 is attributed to prevent ER stress-induced Nrf2 RAAS component upregulation. This mechanism explains the functional dichotomy of Nrf2 in the stressed heart. Thus, Pak2 regulation of Nrf2 homeostasis may present as a potential therapeutic route to alleviate detrimental ER stress and heart failure.